Suitability mapping for watermelon in the Mekong Delta, Cambodia - Villano, Lorena; Raviz, Jeny; Aunario, Sorrel Khalil; Balanza, Jane Girly; Laborte, Alice (International Rice Research Institute, 2024)
"Each crop has specific requirements to grow optimally in a given environment. Biophysical parameters such as climate, land and terrain, as well as, management practices, infrastructure and technological interventions (e.g., irrigation) could affect the suitability and productivity of a crop. Biophysical suitability maps are useful in identifying locations and growing seasons (i.e. planting months) where and when crops can be grown. In addition, recommendations on cropping systems diversification can also be identified from the suitability maps of the priority crops in the Delta. "